Qiyas sebagai Metode Ijtihad dan Implementasinya dalam Transaksi Keuangan Ekonomi Islam Kontemporer - Ummah, Ina Nasihatul; Aziz, Jamal Abdul (Institut Pesantren Sunan Drajat Lamongan, Indonesia, 2025)
Along with the dynamic development of the times, many new products and cases have emerged in the modern economy. Islamic law has established and set boundaries on these issues concerning halal and haram aspects. The Qiyas method is necessary in legal studies to produce fiqh formulations in Islamic economic and financial law. Qiyas is the fourth source of law in Islam; this method of deriving law provides a broad pathway for finding legal foundations for all encountered issues. Viewed from the various types of 'illah, the deepening of law through the method of qiyas must be done carefully and cautiously. The dynamics of development and innovation of Sharia financial contracts in the Sharia economy will certainly become more modern in accordance with the times. Therefore, this poses a challenge for Muslim scholars to address so that it does not become a concern for the community when the application of Sharia finance contracts is packaged in a modern way, which on one hand requires the use of the qiyas method to determine their legal status. This paper aims to explain the concept of qiyas as a method of ijtihad in Islamic law and then examine the implementation of qiyas in contemporary Islamic economic transactions. The type of writing in this article is a library research study using a qualitative method aimed at discussing several themes about the definition of qiyas, the authority of qiyas, the pillars and conditions of qiyas, the types of qiyas, the dynamics of qiyas development, and the implementation of qiyas in contemporary Islamic economic transactions. In this article, it can be concluded that the implementation of Qiyas to determine its legal status can be formulated in the encyclopedia of contemporary sharia financial contracts that use the Qiyas method in determining the ashl and furu’ from the perspective of Islamic law. With transactions and financial products continuously evolving, many aspects of economic transaction activities that did not exist in the past have only emerged in the contemporary context, or it can be said that these transactions have developed from classical to contemporary.